Antioxidant Activity of Three Honey Samples in relation with Their Biochemical Components - Lee Suan Chua; Norul Liza A. Rahaman; Nur Ardawati Adnan; Ti Tjih Eddie Tan (Journal of Analytical Methods in Chemistry)
The antioxidant activities based on the free radical scavenging, reducing power, and bleaching inhibition were investigated for the three commonly used honeys in Malaysia, namely, tualang, gelam, and acacia honey. The antioxidant capacity of the honey samples was correlated with their biochemical constituents such as total phenol, total flavonoid content, and total water-soluble vitamins (vitamin B1, B2, B3, B9, B12, and vitamin C). The total flavonoid content of honey samples was strongly correlated with the three antioxidative processes (–0.9910). In contrast, the total water-soluble vitamins was found to be well correlated with the free radical scavenging activity (). Vitamin B3 was likely to be in the highest concentration, which covered for 69–80% of the total vitamin content. A number of five phenolic acids, three flavonoids, and two organic acids had also been detected from the honey samples using UPLC-MS/MS, without sugar-removal procedure.